دراسة تحليلية وتجريبية للمقطع العرضي التفاضلي لتبعثر رذرفورد - جبور جبور; ملحم جهاد; سعيد هلا (Latakia University Journal -Basic Sciences Series, 2013)
تم، في هذا العمل، تسجيل عدد جسيمات ألفا الصادرة عن منبع من الأمريسيوم-241، والمتبعثرة على وريقات رقيقة من الذهب والألمنيوم بتابعية زاوية التبعثر q (0o – 30o)، باستخدام كاشف نصف ناقل وغرفة تبعثر رذرفورد. تم أيضاً قياس المقطع العرضي التفاضلي عن الناتج عن هذا التبعثر، وحساب العدد الذري للهدف تجريبياً، لكل من الذهب والألمنيوم. مقارنة النتائج التجريبية بالنتائج النظرية يشير إلى تطابق جيد بينهما. In this work, it has been recording the alpha particles emitted from an Amerecium-241 source, and scattered by a gold and Aluminum thin foils as a function of the scattering angle q (0o-30o), using a semiconductor detector and Rutherford scattering chamber. It always has been measuring the differential cross section resulting from this scattering, and experimentally determining the atomic number of Gold and Aluminum. Comparison between experimental and theoretical results shows a good agreement.